(3QSGdI GdYdGeI CHj GdSYhO aj hba Gdefbhds - (3eMeO Hf eMeO Hf eUWai GdYeGOj, Gdehdi CHh GdSYhO,J (B982 (3g` s
(3ChdgG (B:s
(3GdMeO ddg HMb GdMb hYde GdUhGH hHYO aEf hba Gdefbhd JHYkG ddYbGQ chba GdHfGA eY GdbQV hhba GdYHjO hGdKjQGf hBdGJ GdRQGYI s
(3BNQgG (B:s
(3ef MjK GYJHGQg ai Ua BNQ ef Pdc GdMce eYjfg cGYJHGQ GdJYGQa ai UMI hba eYWi HfGA Ydi GYJHGQg ai UMI hba HYVgG efgG Ch CYQafG aGYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B24s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3abg Mfais
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B59 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B301s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdeLGejYs